The Heinle picture dictionary for children : workbook - Korey O'Sullivan, Jill. (Florence : Heinle Cengage Learning, Inc, 2008)
The Heinle Picture Dictionary for Children is the only children's dictionary that presents vocabulary within thematic readings and offers opportunities for multi-level practice of every word introduced to help develop English language skills.
Keywords: Picture dictionaries, English; Children's books